(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Relations of the Khoqand Khanate with the Ottoman Empire begun and developed in the first half of the 19th century. Diplomatic affairs of the Khoqand Khanate with the Ottoman Empire which played the most important role in its flourishing period from the end of the 18th century to 40s of the 19th century are less specially studied. Because, in this epoch the Khoqand Khanate was more developed country in political, cultural and social spheres comparing with other Khanates. The Russian Empire planned to conquer this state firstly. It could be said that early diplomatic relations between the Khoqand Khanate and the Ottoman Empire began between1819-1820. In the Ottoman archives can be found more data about diplomatic reltions of two countries.This article analyzes the relationship between the Khoqand Khanate and the Ottoman Empire on the basis of manuscript sources and Ottoman archival documents.